Estimation of time cost of anti-cancer drugs approved based on comparisons to best supportive care: A cross sectional analysis. (December 2022) - Prasad, Vinay; Olivier, Timothée; Chen, Emerson Y.; Haslam, Alyson
Abstract: Background: Financial costs from cancer treatment are increasingly recognized, but what has historically been underrecognized is the time cost of therapy. We sought to estimate the time burden of anti-cancer drugs approved based on comparisons to best supportive care (BSC), with the assumption that without this drug, a patient could have been treated with observation, home palliative care or hospice services, with minimal time seeking medical care. Methods: We searched all FDA approvals (2009 - March 2022) for randomized trials that used BSC as a treatment option for an anti-tumor drug in the metastatic setting and abstracted data on treatment related activities. We then estimated time spent on these activities using previously calculated times. Results: Of the 13 drugs tested against BSC, nine studies demonstrated an improvement in median OS (median 2.1 months). The median monthly time spent for patients in the intervention arm of BSC trials was 15.8 h. Conclusion: Time is a valuable resource for people who have cancer, but especially for patients who may have few to no remaining treatment options, and yet, we found that patients can spend up to 16 h in anti-cancer drug related activities per month. Policy summary: Because survival outcomes are variable for patients being treated in later lines of therapy, time resources are a valuable consideration in the treatment plan. Highlights: The monthly time spent getting treatment for patients in BSC trials was 15.8 h. Traveling (5.3 h/month) was the most time-intensive trial-related activity. Estimated time spent on treatment-related activities is likely underestimated.